2011
DOI: 10.1007/s11999-010-1332-6
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Bone Regenerate after Intramedullary Femoral Lengthening: Risk Factors and Classification System

Abstract: Level II, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 25 publications
4
60
1
2
Order By: Relevance
“…The mean healing index in our study was 0.91 months/cm, which is better than other results in the literature. Kenawey et al [20] reported a mean healing index of 1.2 months/cm using the ISKD and Catagni et al [7] reported a mean healing index of 1.5 months/cm using the Ilizarov.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean healing index in our study was 0.91 months/cm, which is better than other results in the literature. Kenawey et al [20] reported a mean healing index of 1.2 months/cm using the ISKD and Catagni et al [7] reported a mean healing index of 1.5 months/cm using the Ilizarov.…”
Section: Discussionmentioning
confidence: 99%
“…The other method that has been previously used is the ISKD, which is the only intramedullary device for lengthening that has been in general use in United States. This method is associated with several complications, such as premature or delayed consolidation with difficulties in controlling the distraction rate rhythm, implant breakage, and mechanical failure [9,20,22,35,36]. Mahboubian et al [22] reported complications requiring additional surgeries such as exchange nailing or removal of the ISKD in six of 12 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the main underlying cause of premature consolidation, which is about 12 % for ISKD [51,53,151], compared to below 5 % for all the other implants [16,50,53]. Runaway nails unintentionally lengthen more than 1.5 mm/day, a problem encountered in around 10 % of ISKDs [19,51,52,55]; one patient even underwent accidental 3 cm lengthening during manipulation under anaesthesia [51] and another expanded to 4 cm unintended length during the first 2 weeks [52]. Bolt loosening [63] and problems with locking screws [66] are obstacles without permanent consequences.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
“…runaway nail), age [30 years, smoking, gain [4 cm, osteotomy at the same site of previous trauma or surgery and acute correction of associated deformities may be associated factors [19,53,63]. Partial or complete bony defects have been reported in up to 22 % for ISKD nails [19,51], mostly due to inadvertent higher distraction rates (1.5 vs 1.1 mm). Pseudarthrosis is a nonevent in most series [53,60,62].…”
Section: Outcomes and Complicationsmentioning
confidence: 99%